Características de las mordeduras de canes en pacientes atendidos en un Instituto de Salud Especializado III-2 de Lima, periodo 2017-2020 - Noel P., Mariel Del Rosario (2022)
The aim of the study was to describe dog bite accidents in patients treated at “Hospital Nacional Guillermo Almenara Irigoyen” in Lima during the period between 2017 and 2020. For this, information on dog bite accidents was collected from the epidemiological files of MINSA (format of 2015 and 2017) using an Excel database. The variables included were age group, sex, education level and birthplace (district) of the victim, owner of the aggressor animal; number, type, location, treatment and place of the injury, as well as the district of the accident. The information was analyzed using Stata 15.0 and summarized using descriptive statistics. From 187 epidemiological files, the highest number of reports of dog bite accidents were in male (66.8%), the age group was from 5 to 9 years (74%), occurred in Eastern Lima (46%) and reported during 2019 (79%). Attacks caused by dogs known by the victims predominated and caused severe injuries (97.9%), multiple wounds (47.1%), deep wounds (58.3%) and not infected (60.4%). Likewise, most of the cases were reported the same day of the accident (44.9%) and only required ambulatory care (60.4%).  It’s expected that these results may be useful for the surveillance, control, and prevention of dog bite accidents, and for raising awareness about this problem.